Simulación como herramienta de ayuda para la toma de decisiones empresariales. Un caso práctico - Julio César Puche Regaliza; José Costas Gual; Pablo Arranz Val (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– Business decision making is a critical factor to the viability of companies. In the current more dynamic, global and competitive scenario, this critical factor opens space to wider requirements. Modeling and simulation have traditionally formed a substantial part of the toolkit used to support decision making, especially in the business strategy field. In this paper, our aim is to open a clear perspective on the added value offered by simulation. We first introduce an overview about the process of decision making based on simulation. Next, a case study is developed, in which such steps are reflected to decide whether to implement a PUSH behavior or a PULL behavior in a particular company. The results obtained lead us to the decision to implement PULL instead of PUSH, showing that simulation techniques are a very valuable tool to have in the bank of knowledge in any mature company.
Keywords: C44; C63; D21; 330; decision making; discrete simulation; lean manufacturing